Comparative Efficacy of Rosuvastatin (Low Vs High Dose) in Lowering Low Density Lipoprotein Cholesterol in Intermediate Risk Cardiovascular Patients - Akhtar, Muhammad Abdul Rehman; Siddique, Tahir (Indus Journal of Bioscience Research, 2025)
Background: The enzyme 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibition therapy exists as a prevalent method to control blood lipid levels. Higher statin doses demonstrate better efficacy at decreasing cardiovascular events when compared to lower dosage amounts according to the research findings. International guidelines support the use of high dose rosuvastatin yet adverse effect concerns might inhibit its actual prescription. The study evaluated how low dose rosuvastatin treatment performed against high dose rosuvastatin therapy in patients at intermediate cardiovascular risk. Methodology: The research took place within Medical OPD Lahore General Hospital stretching from July 2024 until January 2025. Researchers distributed 96 patients between Group A which received 10 mg Rosuvastatin and Group B which received 20 mg Rosuvastatin for a duration of three months. Blood tests checked serum creatine phosphokinase (CPK) and low density lipoprotein cholesterol (LDL-C) at both the study start and three months into the trial. The study evaluated effectiveness through LDL-C reductions. Results and Discussion: Group A included 37.5% male participants along with 62.5% female participants whereas Group B comprised 60.4% male participants with 39.6% female participants and their ages showed Group A averaged 49.31±10.96 years while Group B averaged 51.60±11.13 years. Group B participants demonstrated significantly lower mean LDL-C values at 172.94 ± 32.02 mg/dl when compared to Group A at 248.94 ± 53.66 mg/dl (p < 0.05). Group B reached statin efficacy at 85.4% whereas Group A achieved it only at 39.6% (p<0.05). The mean CPK levels in Groups A and B measured at 85.67 ± 19.30 and 74.65 ± 20.89 µg L− but showed statistically significant differences between these values (p < 0.05). High dose rosuvastatin provided more effective LDL-C lowering outcomes than low dose therapy for patients with intermediate cardiovascular risk.